Growing ovarian teratoma syndrome: Case report and literature review - Alzamora, Maria Claudia (2020)
The growing teratoma syndrome (GTS) is a rare condition in which patients with germ cell tumors present an increase in tumor size or the appearance of new lesions, during or after chemotherapy. The hallmark of this tumor is the unique presence of mature teratoma components, as well as tumor marker values that become negative with chemotherapy, and remain low thereafter. We report the case of a 28-yearold female who presented a mixed germ cell tumor of the ovary, for which she underwent surgery and subsequent chemotherapy. Later, she developed multiple pelvic tumors that corresponded to mature teratoma. It was crucial in this patient to identify the syndrome to avoid additional treatment with chemotherapy.